Need for Capacity Building of Farmers in Sarchi Village of Tirthan Valley of Himachal Pradesh - Awasth, Hitul; Thakur, Pooja (Journal of Agricultural Extension Management, 2022)
In Sarchi village of Himachal Pradesh, a majority of people reside in rural areas and depend on natural resources for their livelihood. However, due to climate change, undulating topographical conditions, establishment of projects and lack of irrigation facilities, they are facing many challenges in sustaining their livelihood. In the present study, around 40 per cent of the farmers pointed out climate change as a major constraint in crop production followed by lack of irrigation facilities (33.33%), excessive chemical use (16.67%) and an increase in non farm income (10%). The Himachal Pradesh Horticulture Development Project introduced by the Government of Himachal Pradesh has proved to be a boon for the farmers of this area and has helped around fifty per cent of them to cope up with crop production constraints, while others shifted to vegetable production (30%) and tourism sector (16.67%). Due to the lack of skill and entrepreneurship development programmes in the agriculture sector, the farmers of Sarchi showed great interest in skill development courses like fruit production (36.67%), followed by capacity building in tourism (26.67%), vegetable production (16.66%), beekeeping (10%) and sericulture (10%). The present study focuses on major constraints in crop production faced by farmers of Sarchi and their adaptation to cope with these constraints. It also emphasises the immediate need to impart skill development training to farmers of Sarchi village for sustaining their livelihood